Capacitively coupled contactless conductivity detection for microseparation techniques - recent developments - Kubáň, Pavel; Hauser, Peter C. (Electrophoresis, 2011)
An overview of the developments of capacitively coupled contactless conductivity detection in CE and related techniques over approximately the last 2 years is given. The method has seen strong growth, and diverse new applications are being reported. Besides more advanced techniques on conventional capillaries, these include further developments of detection on lab‐on‐chip devices as well as in miniaturized chromatographic systems and some methods not involving separations. An increasing number of reports are based on the now readily available commercial detectors, but, while few publications on fundamental studies have appeared recently, interesting new approaches on creating low cost devices have also appeared.